The Sprite's Den - Ennis - Hill, Jessica; Caldecott, Elen; Waters, Erica - Jane (ill) (London : Hodder Children's Books, 2017)
What if you had a magic bracelet that allowed you to conjure anything you wanted - out of thin air! Evie's grandma has sent her another parcel. Inside layers of tissue and colourful ribbons is a beautiful bracelet! Evie's going to need the bracelet's powers - and a brave heart - to deal with some mischievous sprites. But she's always ready to have some magical adventures! Evie shares Jessica's determination and drive - an inspiration for kids everywhere
Keywords: Children's Literature - Fiction